Distributed Cat Modeling Based Agile Framework for Software Development - Prakash B; Viswanathan V (Universitas Diponegoro, 2020)
Software development is a hectic process that requires keen understanding and effective model such that the developed software inherits good quality, reliability, and achieves customer satisfaction towards achieving the goals effectively. The effective operation of the software is enabled by modifying the operating modules of the software through a model, like agile. In this paper, the catastrophic and distributed computing models are integrated into the software development step. The proposed model is termed as Distributed Cat model that is developed with the aim to handle the risk factors engaged in various developing stages of the agile model. The risk factors that affect the communication, planning, release, design, coding and testing modules of the agile modules are deeply learned and executed such that the risk factors are tackled by various modules present in the proposed Distributed Cat model. The effectiveness of the proposed model is analyzed based on the performance metrics, such as Index of Integration (IoI) and Usability Goals Achievement Metric (UGAM), for which five products including the hotel management system, Customer relationship Management system (CRM), Rainfall prediction system, Temperature monitoring system, and meta-search system, are employed and analyzed. The analysis is progressed using the parameters, like mean difference, variance, standard devaiation, correlation. The analysis proves that the proposed model offered a great deviation after applying the proposed model contributing a high degree of performance in software development.